2007
DOI: 10.1074/jbc.m704129200
|View full text |Cite
|
Sign up to set email alerts
|

Human Heat Shock Protein 70 Enhances Tumor Antigen Presentation through Complex Formation and Intracellular Antigen Delivery without Innate Immune Signaling

Abstract: Heat shock proteins (HSPs) have shown promise for the optimization of protein-based vaccines because they can transfer exogenous antigens to dendritic cells and at the same time induce their maturation. Great care must be exercised in interpretating HSP-driven studies, as by-products linked to the recombinant generation of these proteins have been shown to mediate immunological effects. We generated highly purified human recombinant Hsp70 and demonstrated that it strongly enhances the cross-presentation of exo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
107
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 120 publications
(111 citation statements)
references
References 82 publications
3
107
1
Order By: Relevance
“…Accordingly, it was shown that the endotoxin contamination in recombinant Hsp70 is common and exclusively responsible for the described proinflammatory properties, including activation of APCs (12)(13)(14)(15)(16). It was also shown that endotoxin-free Hsp70 did not induce APC activation while still effectively delivered antigenic peptides for cross-presentation (17). In a different study, Hsp70 failed to bind to null cells overexpressing either CD14, TLR2, or TLR4 which had previously been associated with the Hsp70-mediated activation of innate immunity (8).…”
Section: Strongly Suggest That Hsp70 Might Dampen Rather Than Provokmentioning
confidence: 99%
“…Accordingly, it was shown that the endotoxin contamination in recombinant Hsp70 is common and exclusively responsible for the described proinflammatory properties, including activation of APCs (12)(13)(14)(15)(16). It was also shown that endotoxin-free Hsp70 did not induce APC activation while still effectively delivered antigenic peptides for cross-presentation (17). In a different study, Hsp70 failed to bind to null cells overexpressing either CD14, TLR2, or TLR4 which had previously been associated with the Hsp70-mediated activation of innate immunity (8).…”
Section: Strongly Suggest That Hsp70 Might Dampen Rather Than Provokmentioning
confidence: 99%
“…Recombinant Hsp70 Proteins-Recombinant human (rhu)-Hsp70 protein was either purchased from Stressgen, Victoria, BC, Canada (ESP-555) or was prepared in our own laboratory as described (17). After ADP affinity chromatography, buffer was exchanged using PD10 columns followed by extensive dialysis (48 h, 5000ϫ buffer volume) and diafiltration (Vivaspin 20, 30,000 MWCO PES, Sartorius Stedim Biotech).…”
Section: Methodsmentioning
confidence: 99%
“…To assess the influence of nucleotide carryover, rhuHsp70 preparations were used after PD10 column and diafiltration with a less intensive dialysis step (Hsp70/nc ϩ ). Endotoxin was depleted, as described (17). Only proteins with endotoxin below 0.5 EU/mg rhuHsp70 were used.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations